2011
DOI: 10.1016/j.devcel.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of Lysosomal Exocytosis Promotes Cellular Clearance

Abstract: SummaryLysosomes are cellular organelles primarily involved in degradation and recycling processes. During lysosomal exocytosis, a Ca2+-regulated process, lysosomes are docked to the cell surface and fuse with the plasma membrane (PM), emptying their content outside the cell. This process has an important role in secretion and PM repair. Here we show that the transcription factor EB (TFEB) regulates lysosomal exocytosis. TFEB increases the pool of lysosomes in the proximity of the PM and promotes their fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
629
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 619 publications
(680 citation statements)
references
References 40 publications
19
629
1
5
Order By: Relevance
“…Our data show that oral trehalose administration protects neurons from the pathological accumulation of glycosaminoglycans and that autophagic vacuoles – the putative sites of glycosaminoglycan accumulation – are dramatically cleared from neurons. Thus, if appropriately stimulated, neurons can restore the clearance of intralysosomal material even in the absence of catabolic enzymes, most likely through processes such as lysosomal exocytosis [19]. It is noteworthy that possible therapeutic applications of trehalose may be challenged by the presence of trehalase, a specific trehalose-degrading enzyme, in the intestine, kidney, and other organs in mammals [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show that oral trehalose administration protects neurons from the pathological accumulation of glycosaminoglycans and that autophagic vacuoles – the putative sites of glycosaminoglycan accumulation – are dramatically cleared from neurons. Thus, if appropriately stimulated, neurons can restore the clearance of intralysosomal material even in the absence of catabolic enzymes, most likely through processes such as lysosomal exocytosis [19]. It is noteworthy that possible therapeutic applications of trehalose may be challenged by the presence of trehalase, a specific trehalose-degrading enzyme, in the intestine, kidney, and other organs in mammals [66].…”
Section: Discussionmentioning
confidence: 99%
“…TFEB (transcription factor EB) is a master regulator of lysosomal pathways, governing lysosomal biogenesis and metabolism [17], autophagy [18], and lysosomal exocytosis [19] and proteostasis [20]. TFEB overexpression promotes lysosomal proliferation and enhances degradative capabilities against lysosomal or autophagic substrates (such as glycosaminoglycans, polyQ-expanded HTT (huntingtin), and ceroid lipopigments), and rescues affected neurons in animal models of proteinopathies [17,2127].…”
Section: Introductionmentioning
confidence: 99%
“…Using whole-endolysosome recordings, we recently found that TRPML1 conducts both Ca 2+ and Fe 2+ , and can be activated specifically by PI(3,5)P 2 but not other phosphoinositides (12,16,17). Interestingly, TRPML1 can also be detected in nonlysosome cellular compartments, in particular, the PM, upon exocytosis from the Golgi apparatus (the biosynthetic pathway) (13,14) or the lysosome (lysosomal exocytosis) (18,19). Indeed, when lysosomal exocytosis was dramatically increased by a constitutively active TRPML1 mutant (TRPML1 Va ), large whole-cell TRPML1 currents were detected (18).…”
Section: Trp Channel | Mucolipinmentioning
confidence: 98%
“…The inhibitory effects of the PM-specific phosphoinositides PI (4,5)P 2 , PI(3,4,5)P 3 , and PI(3,4)P 2 , the stimulatory effect of LELspecific PI(3,5)P 2 , and the lack of effect of Golgi-specific PI(4)P or early endosome-specific PI(3)P, indicate that a tight regulatory mechanism controls TRPML1 activity during membrane trafficking. TRPML1 plays a key role in Ca 2+ -dependent lysosomal exocytosis, a cellular process that is important for membrane repair and neurotransmitter release (18,19). Phosphoinositidemediated activation of TRPML1 may lead to lysosomal Ca 2+ release, triggering lysosome exocytosis (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…ML1-mediated lysosomal Ca 2+ release may regulate many aspects of lysosomal trafficking, including lysosome to trans-Golgi-network (TGN) retrograde trafficking, autophagosome-lysosome fusion, lysosome reformation, and lysosomal exocytosis (15,19,22,23). Moreover, it has been demonstrated that nutrient starvation affects phosphoinositide dynamics and Ca 2+ signaling (16,18,24).…”
Section: Significancementioning
confidence: 99%